Medicinal plants contain mucilage used in traditional Persian medicine (TPM). (April 2015) - Ameri, Ahmad; Heydarirad, Ghazaleh; Mahdavi Jafari, Jamileh; Ghobadi, Ali; Rezaeizadeh, Hossein; Choopani, Rasool
Abstract Context: Conventional therapies using mucilage plants greatly used by practitioners in Iran. The usage of mucilages is rooted in traditional knowledge with a history of more than 4000 years. Scientific assessment of these historical documents could be valuable for finding new potential usage in the current medicine. Objective: This study assembled an inventory of mucilage plants considered important therapeutic aids for alleviating the ailments in ancient Persian medicine and compared therapeutic applications of ancient times with current findings of medicinal mucilages in the same plant species. Methods: A literature search compiled some main traditional manuscripts of Persian medicine, including the book of AlHavi, Canon of Medicine, Zakhireh-iKharazmshahi, Qarabadine-kabir, Tohfat ol Moemenin, and Makhzan-ol-advieh, and select mucilage plants used in treating the mouth and respiratory system disorders. Also, current investigations on related subjects were considered through a search of the Pub Med and Google Scholar databases. Results: In Iran, the application of medicinal plants contains mucilage date back to ancient times. In mentioned medieval Persian books, 20 medicinal plants containing mucilage were identified. Mucilages have been traditionally used via oral or topical routes for a variety of disorders. According to this study, most of the cited medicinal plant species were used for their mucilaginous, anti-inflammatory, and anti-oxidant effects. Conclusions: A scientific evaluation of these historical documents can give an insight into the ideas of the past and be valuable in finding new data on clinical use of the mucilages that should lead to future opportunities to investigate their potential medicinal use.